Analysis of the Link between Metacognitive Beliefs and Academic Health-oriented Lifestyle Preventive Behaviours Mediated by Self-efficacy during the COVID-19 Pandemic - Fatemeh Moradi; Sara Aghaei Sabet; Sahar Soufi (Multidisciplinary Journal for Education, Social and Technological Sciences, 2022)
The outbreak of the coronavirus and its ramifications, including lockdown and shutting down of many learning centers magnified the necessity of turning to virtual learning, has given rise to concerns about students’ learning and their reaction to the new teaching methods and the challenges they entail. The present study attempts to examine the link between metacognitive beliefs and behaviors that prevent health-oriented lifestyles through academic self-efficacy during the COVID-19 pandemic. The statistical sample consisted of 239 randomly selected undergraduate students of engineering at Azad University of Shahre-e Rey in the second semester of 1399-1400. The data were gathered using academic health-oriented life style test Salehzadeh et al. (2018) Academic Self-Efficacy Beliefs Questionnaire (ASEBQ), and Wells’ Metacognition Questionnaire-30 (MCQ-30). Findings of the study indicated that metacognitive beliefs are related to behaviors preventing academic health-oriented life style factors, such as learned helplessness and effort withdrawal, through self-efficacy. It is suggested that, According to the positive relationship that exists between metacognitive strategies and academic achievement. As well as these strategies are scalability learners need to be trained in skills such as self-regulation self- monitoring planning and goal setting. Until they dominate decided cognitive strategies and professors can also encourage students to use orientation by designing assignments, teaching study strategies, and using new teaching methods